Can we make cannabis safer?. (August 2017) - Englund, Amir; Freeman, Tom P; Murray, Robin M; McGuire, Philip
Summary: Cannabis use and related problems are on the rise globally alongside an increase in the potency of cannabis sold on both black and legal markets. Additionally, there has been a shift towards abandoning prohibition for a less punitive and more permissive legal stance on cannabis, such as decriminalisation and legalisation. It is therefore crucial that we explore new and innovative ways to reduce harm. Research has found cannabis with high concentrations of its main active ingredient, δ-9-tetrahydrocannabinol (THC), to be more harmful (in terms of causing the main risks associated with cannabis use, such as addiction, psychosis, and cognitive impairment) than cannabis with lower concentrations of THC. By contrast, cannabidiol, which is a non-intoxicating and potentially therapeutic component of cannabis, has been found to reduce the negative effects of cannabis use. Here, we briefly review findings from studies investigating various types of cannabis and discuss how future research can help to better understand and reduce the risks of cannabis use.